Mutual Coupling Reduction between Asymmetric Reflectarray Resonant Elements - M. Hashim Dahri; M. H. Jamaluddin; M. Inam; M. R. Kamarudin (International Journal of Electrical and Computer Engineering (IJECE), 2018)
A physically asymmetric reflectarray element has been proposed for wide band operations. The dual resonant response has been introduced by tilting one side of the square path element. The numerical results have been analyzed in the frequency band between 24GHz to 28GHz where a reflection phase range of more than 600° has been achieved. The proposed asymmetric element can produce mutual coupling with adjacent elements on a reflectarray. This effect has been monitored by placing the elements in a mirror configuration on the surface of reflectarray. The single unit cell element results have been compared with conventional 4 element unit cell and proposed mirroring element configuration. The proposed mirroring element technique can be used to design a broadband reflectarray for high gain applications.